Method for preparing high-strength concrete by pre-coating modification of coal gangue aggregate
Patent Information
- Application Number
- CN202611271056.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-20
- Publication Date
- 2026-10-23
AI Technical Summary
[0005]为了弥补以上不足,本发明提供了一种煤矸石骨料预包覆改性制备高强混凝土的方法,旨在改善了现有技术中煤矸石骨料改性技术主要存在包覆层无法自致密导致强度不足、养护过程中易发生颗粒粘结团聚,以及改性骨料与混凝土基体之间界面粘结力薄弱的问题
1.本发明能够实现包覆层的自致密化,提高改性骨料的结构强度,具体而言,中间层内部的自由流体向内核层与外部隔离层方向同步迁移,导致中间层内部的自由流体体积总量下降。中间层内部包含的普通硅酸盐水泥颗粒、矿渣粉颗粒与硅灰颗粒在流体体积缩减产生的边界收缩作用下发生相对位移,这些微观颗粒互相靠拢,缩减固体颗粒之间的间距尺寸,固液双相协同重塑模块在无外界机械压实外力介入的条件下,减小中间层内部的孔隙容积,完成复合改性浆体的结构致密化过程。
Smart Images

Figure CN122958093A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of building materials, and more particularly to a method for preparing high-strength concrete by pre-coating and modifying coal gangue aggregate. Background Technology
[0002] Coal gangue is a solid waste generated during coal mining and washing. Using it as coarse aggregate in concrete preparation is an important way to realize the resource utilization of solid waste. However, due to the problems of high porosity, numerous surface microcracks, and high water absorption of raw coal gangue aggregate, it is usually necessary to use cementitious material slurry to coat and modify its surface to improve the physical properties of the aggregate. However, existing coal gangue aggregate modification technologies still have the following shortcomings in practical applications: Existing slurry coating methods often result in coating layers with high porosity when treating aggregates. Without external mechanical compaction, the slurry coating the aggregate surface contains a lot of free water, and the spacing between solid particles in the slurry is large, making it impossible to automatically achieve structural densification. This leads to insufficient structural strength of the modified aggregate's external coating layer, making it prone to damage when subjected to external forces, thus limiting the improvement of the overall strength of concrete.
[0003] During the static curing process of aggregates coated with slurry, adjacent aggregate particles inevitably come into contact in a stacked state. Due to the hydration activity of the slurry on the aggregate surface, the slurry at the contact points will fuse together, resulting in cross-particle cementation during the hydration and hardening stage. This leads to a large amount of aggregate sticking together and agglomerating into lumps. This agglomeration phenomenon destroys the independence of aggregate particles and seriously affects the material dispersion and gradation control during subsequent concrete preparation.
[0004] When modified aggregates that have undergone curing are mixed into the concrete matrix, the interface between the surface of the modified aggregates and the fresh mortar often becomes a weak point in the structure. The surface of the existing modified aggregates typically lacks sustained reactivity after curing, failing to effectively induce the hydration products within the fresh mortar to extend and interweave to the aggregate surface. This results in the modified aggregates and the fresh mortar matrix relying solely on physical adhesion, with weak interfacial bonding, failing to establish continuous and high-strength chemical bonds, ultimately affecting the overall mechanical properties of the concrete. Summary of the Invention
[0005] To overcome the above deficiencies, this invention provides a method for preparing high-strength concrete by pre-coating and modifying coal gangue aggregate. The aim is to improve the existing coal gangue aggregate modification technology, which mainly suffers from insufficient strength due to the inability of the coating layer to self-densify, easy particle agglomeration during curing, and weak interfacial bonding between the modified aggregate and the concrete matrix.
[0006] To achieve the above objectives, the present invention adopts the following technical solution: a method for preparing high-strength concrete by pre-coating and modifying coal gangue aggregate, comprising the following steps: Step 1: Obtain raw coal gangue aggregate, and perform fluid soaking and surface physical dehydration treatment on the raw coal gangue aggregate to produce first surface-dry saturated aggregate; the first surface-dry saturated aggregate is in a physical state in which there is no free water on the surface and the internal pores are saturated with fluid. Step 2: Obtain the first part of cement, slag powder, silica fume and the first part of mixing water; mix the first part of cement, part of the slag powder, part of the silica fume and the first part of mixing water to produce a composite modified slurry in a fluid suspension state; extract the remaining slag powder and mix it with the remaining silica fume to produce a homologous active dry powder in a solid dry powder state. Step 3: Place the first surface-dry saturated aggregate into the composite modified slurry and perform physical stirring to produce wet initial-coated aggregate; allow the wet initial-coated aggregate to stand to drain excess slurry, and during the initial standing process, sprinkle the homologous active dry powder onto the surface of the wet initial-coated aggregate, and then apply mechanical rolling action to produce powder-embedded solid aggregate; so that within the structure system of powder-embedded solid aggregate, the free fluid contained in the composite modified slurry migrates to the outside and inside to achieve densification; Step 4: Apply constant temperature and humidity conditions to the powder-embedded solid aggregate for curing reaction treatment. After the curing reaction is completed, cured modified aggregate is produced. Then, the cured modified aggregate is subjected to secondary soaking and surface dehydration to block the fluid absorption path on the surface of the cured modified aggregate and transform the cured modified aggregate into a second surface-dry saturated modified aggregate. Step 5: Control the mixing amount of the second surface-dry saturated modified aggregate and the natural crushed stone coarse aggregate according to the preset volume ratio, and mix the second surface-dry saturated modified aggregate and the natural crushed stone coarse aggregate. Add river sand, the second part of cement, water-reducing agent and the second part of mixing water for segmented dry and wet mixing. After the mixing mixture is filled and shaped, physically vibrated and cured at constant temperature, the high-strength modified concrete product is output.
[0007] As a further description of the above technical solution: Step one, the process of performing fluid soaking and surface physical dehydration treatment on the raw coal gangue aggregate, includes: Untreated block coal gangue is mechanically crushed and screened in multiple stages to retain continuously graded particles with a particle size range of 5 mm to 20 mm as the original coal gangue aggregate. The raw coal gangue aggregate is placed into a soaking tank pre-filled with clean water, and the height of the clean water is controlled to exceed the top layer of the raw coal gangue aggregate. The raw coal gangue aggregate is kept submerged in the clean water for 48 hours, forming a fluid saturation zone in the internal structure of the raw coal gangue aggregate. At the end of the soaking operation, the raw coal gangue aggregate is removed from the soaking tank and placed on a permeable net to perform a static water removal operation. The outer surface of the raw coal gangue aggregate is physically wiped using a flexible water-absorbing wiping component to remove the free water layer and produce the first surface-dry saturated aggregate.
[0008] As a further description of the above technical solution: In step two, the first portion of cement is ordinary Portland cement, the slag powder is S95 grade slag powder, and the silica fume is 92 grade silica fume. The material metering operation follows the following proportioning principle: The ratio of the total mass of the ordinary silicate cement to the total mass of the S95 grade slag powder is set to 9:1, and the ordinary silicate cement and the S95 grade slag powder are combined to form a composite cementitious material base. The total mass of the added Grade 92 silica fume is controlled to be 5% of the total mass of the composite cementitious material substrate; The water-cement ratio is set to 0.5, which means that the ratio of the mass of the first batch of mixing water to the total mass of the composite cementitious material substrate and the grade 92 silica fume is 0.5. The internal material mass ratio of the homologous active dry powder is controlled such that the mass of the remaining 92-grade silica fume extracted is 5% of the mass of the remaining S95-grade slag powder extracted.
[0009] As a further description of the above technical solution: The specific process of step two includes: The S95 grade slag powder is divided into a first slag powder portion as part of the slag powder and a second slag powder portion as the remaining slag powder, and the 92 grade silica fume is divided into a first silica fume portion as part of the silica fume and a second silica fume portion as the remaining silica fume. All of the ordinary silicate cement, the first slag powder portion, the first silica fume portion, and all of the first portion of mixing water are fed into a mixing device for mixing, so that the solid particles are mixed in the first portion of mixing water to form a suspended liquid phase, and the suspended liquid phase is output as the composite modified slurry. The second slag powder portion and the second silica fume portion are fed into a dry powder mixing device to perform physical grinding and stirring operations, and are uniformly mixed to produce the homologous active dry powder.
[0010] As a further description of the above technical solution: The specific preparation process in step three includes: The first surface-dry saturated aggregate is put into the mixing device in operation, so that the composite modified slurry covers the outer surface of the first surface-dry saturated aggregate to form a liquid coating layer, and the wet initial coated aggregate is produced. The wet initial coated aggregate is conveyed to a screen component with a physical mesh structure and laid in a single layer, so that the surface free slurry is separated through the mesh structure by gravity. The homologous active dry powder is sprayed onto the wet initial coating aggregate in a dispersed powder flow state through the atomizing sieving structure of the powder spreading device, so that the particles of the homologous active dry powder adhere to the outside of the liquid coating layer. The screen component is controlled to perform physical tumbling action by means of a mechanical drive assembly, so that the homologous active dry powder particles attached to the outside of the liquid coating layer are embedded into the surface structure of the liquid coating layer under the action of mechanical rolling force, producing the powder embedded solid aggregate.
[0011] As a further description of the above technical solution: Within the powder-embedded solid aggregate structure system, the first surface-dry saturated aggregate constitutes the core layer, the composite modified slurry constitutes the intermediate layer, and the homologous active dry powder particles constitute the outer isolation layer. The densification mechanism in step three includes: The powder-embedded solid aggregate is kept in a static state so that the core layer, which is in a fluid saturation state, can generate water absorption potential energy for the free fluid inside the intermediate layer. In the dry state, the homologous active dry powder particles in the outer isolation layer come into contact with each other to form a stacked structure, so that the gaps between the particles inside the stacked structure form capillary channels and generate capillary water absorption potential energy. The free fluid inside the intermediate layer is pulled towards the core layer and the outer isolation layer by the bidirectional capillary water absorption potential energy, resulting in the reduction of fluid volume and the boundary contraction effect. This causes the solid particles contained in the intermediate layer to undergo relative displacement and move closer to each other, thus completing the structural densification of the composite modified slurry.
[0012] As a further description of the above technical solution: The specific process of step four includes: A ventilator is used to provide airflow to the ventilation and drying components and maintain room temperature, so that the single-layer flat-laid powder embedded solid aggregate is kept in a static state for 2 hours. The outermost homologous active dry powder particles absorb moisture to form a microparticle isolation shell with no bonding strength. The powder-embedded solid aggregate is transported to a standard curing chamber, where a constant temperature of 20 degrees Celsius and a relative humidity of over 95% are provided by a temperature and humidity control device. The curing time is set to 28 days to produce the solidified modified aggregate. The cured modified aggregate is transferred into a secondary soaking tank filled with clean water, and the soaking time is controlled to be 24 hours to saturate the surface capillaries. Then it is removed and placed on a permeable net, and a flexible water-absorbing wiping component is used to physically wipe it to remove the free water layer attached to the outer surface, producing the second surface-dry saturated modified aggregate.
[0013] As a further description of the above technical solution: In step five, the calculation process for controlling the mixing amount includes: Determine the total volume of coarse aggregate per cubic meter and control the volume replacement rate to be within the range of 20% to 60%. According to the equal volume substitution calculation rule, the volume of modified aggregate is calculated by multiplying the total volume of coarse aggregate per cubic meter by the volume substitution rate, and the volume of natural crushed stone is calculated by multiplying the total volume of coarse aggregate per cubic meter by the difference between 1 and the volume substitution rate. Obtain the apparent density of the modified aggregate and the apparent density of the natural crushed stone. Multiply the volume of the modified aggregate by the apparent density of the modified aggregate to obtain the feed mass of the modified aggregate. Multiply the volume of the natural crushed stone by the apparent density of the natural crushed stone to obtain the feed mass of the natural crushed stone.
[0014] As a further description of the above technical solution: Step five, the process of segmented dry and wet mixing, includes: The modified aggregate and the natural crushed stone are extracted according to the mass of the modified aggregate and the mass of the natural crushed stone, respectively, and the river sand of the corresponding mass is extracted and transported into the mixing equipment to start the rotation and perform dry mixing. After the dry mixing action is completed, the second part of cement corresponding to the feed mass is extracted and fed into the mixing equipment for secondary dry mixing to produce a dry mixture. The second portion of mixing water and the water-reducing agent are extracted and simultaneously injected into the mixing equipment containing the dry mixture to perform a wet mixing operation. The duration of the wet mixing operation is greater than or equal to 2 minutes, producing a fluid concrete mixture with fluidity.
[0015] As a further description of the above technical solution: Step five, the process of filling and molding, physical vibration and constant temperature curing includes: The fluid concrete mixture is poured into the mold, and a high-frequency mechanical vibration is applied by a mechanical vibration table to expel gas and produce a dense molded specimen. After covering the surface with a moisturizing film at room temperature and maintaining a static state for 24 hours, the molding mold is removed to obtain the demolded concrete substrate. The demolded concrete substrate is then transported to a constant temperature standard curing room, where the ambient temperature is controlled at 20±2 degrees Celsius and the relative humidity is greater than or equal to 95%. The goal is to enable silica fume particles in an incompletely hydrated state to form nucleation nodes for crystal growth within the demolded concrete matrix, allowing hydration products to form an interwoven crystal structure at the interface, establishing a continuous chemically bonded transition layer, and producing the high-strength modified concrete product after a 28-day curing period.
[0016] The present invention has the following beneficial effects: 1. This invention enables the self-densification of the coating layer, improving the structural strength of the modified aggregate. Specifically, the free fluid inside the intermediate layer migrates synchronously towards the core layer and the outer isolation layer, resulting in a decrease in the total volume of free fluid inside the intermediate layer. The ordinary silicate cement particles, slag powder particles, and silica fume particles contained within the intermediate layer undergo relative displacement under the boundary contraction caused by the fluid volume reduction. These micro-particles move closer together, reducing the spacing between solid particles. The solid-liquid two-phase synergistic reshaping module reduces the pore volume inside the intermediate layer without external mechanical compaction, completing the structural densification process of the composite modified slurry.
[0017] 2. This invention can prevent aggregates from agglomerating and sticking during the curing stage, ensuring the independent molding of aggregate particles. During the hydration, solidification, and sealing stage, the homologous active dry powder particles on the outermost side of the powder-embedded solid aggregate absorb some of the water seeping out of the composite modified slurry. After absorbing water, the homologous active dry powder particles form a microparticle isolation shell on the outermost side of the powder-embedded solid aggregate. This microparticle isolation shell covers the surface of the composite modified slurry and does not have structural bonding strength itself. It can prevent the composite modified slurry inside adjacent powder-embedded solid aggregates from spatially contacting each other, thus avoiding cross-particle matrix cross-linking of the composite modified slurry during the hydration and hardening process.
[0018] 3. This invention can enhance the interfacial bond between modified aggregate and concrete matrix, and improve the mechanical properties of concrete. In a constant temperature standard curing chamber, the 92-grade silica fume particles remaining on the surface of the modified aggregate in the second dry saturated state come into contact with the mortar matrix. The 92-grade silica fume particles in the incompletely hydrated state form nucleation nodes for crystal growth inside the demolded concrete matrix. The hydration products generated by ordinary silicate cement extend to the surface of the modified aggregate in the second dry saturated state through the nucleation nodes and form a crystal interwoven structure in the interface area. This crystal interwoven structure establishes a continuous chemical bonded transition layer around the modified aggregate in the second dry saturated state. Attached Figure Description
[0019] Figure 1 This is a system diagram of coal gangue aggregate modification and concrete preparation according to the present invention; Figure 2 This is a logic diagram of the mixing of aggregate and matrix material in this invention; Figure 3 This is a logic diagram of the gelling material and fluid separation of the present invention. Detailed Implementation
[0020] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0021] Reference Figures 1-3 This invention provides a method for preparing high-strength concrete by pre-coating and modifying coal gangue aggregate. The method for preparing high-strength concrete by pre-coating and modifying coal gangue aggregate relies on a coal gangue aggregate modification and concrete preparation system. The coal gangue aggregate modification and concrete preparation system includes a substrate fluid wetting module, a modified phase material preparation module, a solid-liquid two-phase synergistic reshaping module, a hydration solidification and sealing module, and a multiphase matrix forming module, which are logically connected in sequence.
[0022] The substrate fluid wetting module receives raw coal gangue aggregate and performs fluid soaking and surface physical dehydration treatment on the raw coal gangue aggregate. After being processed by the substrate fluid wetting module, the raw coal gangue aggregate outputs aggregate in a first surface dry saturated state. The aggregate in the first surface dry saturated state is in a physical state where there is no free water on the surface and the internal pores are saturated with fluid. The aggregate in the first surface dry saturated state stores liquid water in its internal micro-pore structure.
[0023] The modified phase material preparation module independently prepares the composite modified slurry and the homologous active dry powder. The modified phase material preparation module receives cement, slag powder, silica fume and mixing water. The modified phase material preparation module mixes and stirs the cement, part of the slag powder, part of the silica fume and mixing water to produce the composite modified slurry. The modified phase material preparation module extracts the remaining slag powder and silica fume and mixes them to produce the homologous active dry powder. The composite modified slurry is in a fluid suspension state, and the homologous active dry powder is in a solid dry powder state. The homologous active dry powder components do not contain cement components and fluid components.
[0024] The solid-liquid two-phase synergistic reshaping module obtains the first surface-dry saturated aggregate, the composite modified slurry, and the homologous active dry powder, respectively. The solid-liquid two-phase synergistic reshaping module places the first surface-dry saturated aggregate into the composite modified slurry and performs physical stirring. The composite modified slurry is attached to the outside of the first surface-dry saturated aggregate to produce wet-state initially coated aggregate.
[0025] The solid-liquid dual-phase synergistic reshaping module allows wet, initially coated aggregates to stand to leach out excess slurry. During the initial standing process, homologous active dry powder is sprinkled onto the surface of the wet, initially coated aggregates. Subsequently, mechanical rolling is applied to produce powder-embedded solid aggregates. Within the powder-embedded solid aggregate structure system, the first surface-dry saturated aggregates form the core layer, and the composite modified slurry forms the intermediate layer surrounding the core layer. Homologous active dry powder particles adhere to the surface of the composite modified slurry, forming an external isolation layer. The core layer of the powder-embedded solid aggregates is in a fluid-saturated physical state, while the external isolation layer is in a dry physical state. The free fluid contained within the composite modified slurry in the intermediate layer migrates towards the core layer and the external isolation layer, achieving the densification process of the composite modified slurry.
[0026] The hydration-curing-sealing module receives powder-embedded solid aggregate and applies constant temperature and humidity conditions to it for curing reaction. The homologous active dry powder on the surface of the powder-embedded solid aggregate absorbs moisture to form an isolation structure without bonding strength, blocking direct contact between particles. After the curing reaction is completed, cured modified aggregate is produced. The hydration-curing-sealing module then performs a second soaking and surface dehydration on the cured modified aggregate, transforming it into a second surface-dry saturated modified aggregate, thus sealing the fluid absorption path on the surface of the cured modified aggregate.
[0027] The multiphase matrix forming module receives modified aggregate in a second dry saturated state and natural crushed stone coarse aggregate. The multiphase matrix forming module controls the mixing amount of the modified aggregate in the second dry saturated state and natural crushed stone coarse aggregate according to the preset volume ratio parameters. The multiphase matrix forming module mixes the modified aggregate in the second dry saturated state and natural crushed stone coarse aggregate, and adds river sand, ordinary silicate cement, water-reducing agent and mixing water for segmented dry and wet mixing. The mixed mixture goes through filling and molding, physical vibration and constant temperature curing steps to output high-strength modified concrete finished product.
[0028] During the process of fluid soaking and surface physical dehydration of raw coal gangue aggregate in the base fluid infiltration module, the base fluid infiltration module uses the internally configured crushing and screening mechanism to obtain untreated block coal gangue for mechanical crushing and multi-stage screening. The base fluid infiltration module uses the crushing and screening mechanism to screen and retain continuous graded particles with a particle size range of 5mm to 20mm. The base fluid infiltration module uses the continuous graded particles within this particle size range as raw coal gangue aggregate.
[0029] The base fluid wetting module puts the raw coal gangue aggregate into the soaking tank inside the base fluid wetting module. The soaking tank is pre-filled with clean water. The base fluid wetting module controls the height of the clean water to exceed the top layer of the raw coal gangue aggregate, so that the raw coal gangue aggregate is in a completely submerged state. The base fluid wetting module sets and maintains the submersion time of the raw coal gangue aggregate in the clean water for up to 48 hours.
[0030] The internal physical structure of undisturbed coal gangue aggregate contains microcracks and capillary channels. During the set immersion period, water seeps into the microcracks and capillary channels inside the undisturbed coal gangue aggregate through capillary force. The volume of the microcracks and capillary channels inside the undisturbed coal gangue aggregate reaches the upper limit of fluid filling, forming a fluid saturation zone in the internal structure of the undisturbed coal gangue aggregate.
[0031] When the soaking operation is completed, the base fluid wetting module controls the first material transfer mechanism configured inside to remove the raw coal gangue aggregate from the soaking tank and place it on the permeable net of the base fluid wetting module to perform a static water removal operation. The base fluid wetting module uses the flexible water-absorbing wiping component configured inside to physically wipe the outer surface of the raw coal gangue aggregate to remove the free water layer attached to the outer surface of the raw coal gangue aggregate.
[0032] After the above physical wiping action, the base fluid wetting module produces the first surface-dry saturated aggregate. The outer surface of the first surface-dry saturated aggregate is in a physical state without liquid water adhering to it, and the internal capillary channels of the first surface-dry saturated aggregate maintain a physical state of liquid water saturation, blocking the physical transmission path of the first surface-dry saturated aggregate to continue absorbing external fluid in subsequent processing steps.
[0033] During the process of mixing cement, slag powder, silica fume and mixing water to produce composite modified slurry in the modified phase material preparation module, the modified phase material preparation module performs material metering operations according to the set proportion parameters.
[0034] The cement obtained by the modified phase material preparation module is P·O42.5 grade ordinary Portland cement, the slag powder obtained by the modified phase material preparation module is S95 grade slag powder, the silica fume obtained by the modified phase material preparation module is 92 grade silica fume, and the mixing water obtained by the modified phase material preparation module is defined as mixing water.
[0035] The modified phase material preparation module sets the total mass ratio of ordinary silicate cement to S95 grade slag powder to be 9:1. Ordinary silicate cement and S95 grade slag powder are combined to form a composite cementitious material base.
[0036] The modified phase material formulation module determines the total mass of Grade 92 silica fume added based on the total mass of the composite cementitious material substrate. The module controls the total mass of Grade 92 silica fume added to be 5% of the total mass of the composite cementitious material substrate, and sets the total mass of ordinary Portland cement to be... The total mass of S95 grade slag powder is set as follows: The total mass of grade 92 silica fume is set as follows: The system-level total mass ratio formula for materials, followed by the metering operation performed by the modified phase material preparation module, is as follows:
[0037]
[0038] The modified phase material preparation module sets the water-cement ratio parameter to 0.5. The water-cement ratio parameter is defined as the ratio of the mass of mixing water to the total mass of all solid cementitious materials (i.e., the composite cementitious material substrate and the sum of Grade 92 silica fume). The mass of mixing water is set to... The rigorous calculation formula for controlling the quality of mixing water in the modified phase material preparation module is as follows:
[0039] To meet the requirements of subsequent composite encapsulation and powder embedding, the modified phase material preparation module pre-divides the S95 grade slag powder into a first slag powder portion (mass of which is...) for slurry preparation. ) and the second slag powder portion used for spreading (mass of ), and satisfy Simultaneously, the 92-grade silica fume was divided into the first silica fume portion for pulp preparation (mass of...). ) and the second silica fume portion used for spreading (mass is ), and satisfy .
[0040] After the material metering and allocation are completed, the modified phase material preparation module will add all the ordinary Portland cement (by mass) The first slag powder portion, the first silica fume portion, and the mixing water (by mass) The internal stirring equipment performs a stirring operation, and the solid particles are mixed in the mixing water to form a suspended liquid phase.
[0041] The modified phase material preparation module outputs a suspended liquid phase as a composite modified slurry. Inside the composite modified slurry, tiny particles of the first silica fume portion fill the voids between ordinary silicate cement particles, forming a liquid-phase particle suspension structure.
[0042] During the process of extracting and mixing the remaining slag powder with silica fume in the modified phase material preparation module to produce homologous active dry powder, the modified phase material preparation module performs a dry powder mixing operation, and obtains the aforementioned separated second slag powder portion (mass of...). ) and the second silica fume portion (mass is Both materials are in a dry physical state without free liquid moisture.
[0043] The modified phase material formulation module maintains the consistency of the ratio between the dry powder system and the overall composite system. The metering equipment within the modified phase material formulation module controls the internal material mass ratio of the homologous active dry powder according to the following formula:
[0044] The total mass of the homologous active dry powder is set as follows: The formula for calculating the total mass of homologous active dry powder controlled by the modified phase material formulation module is as follows:
[0045] After the metrological verification is completed, the modified phase material preparation module inputs the second slag powder part and the second silica fume part into the dry powder mixing equipment inside the modified phase material preparation module to perform physical grinding and stirring operations, and uniformly mix to produce homogeneous active dry powder.
[0046] The homologous active dry powder does not contain cement components or fluid components. The modified phase material preparation module outputs the homologous active dry powder and delivers it to the solid-liquid dual-phase synergistic reshaping module as a spreading medium in the state of solid dry powder.
[0047] In the solid-liquid two-phase synergistic reshaping module, the first surface-dry saturated aggregate is placed into the composite modified slurry and physically stirred. During the process of producing wet initial-coated aggregate by attaching the composite modified slurry to the outside of the first surface-dry saturated aggregate, the solid-liquid two-phase synergistic reshaping module injects the composite modified slurry into the stirring device inside the solid-liquid two-phase synergistic reshaping module.
[0048] The solid-liquid two-phase synergistic reshaping module controls the stirring device to be in operation. The solid-liquid two-phase synergistic reshaping module puts the first surface dry saturated aggregate into the stirring device in operation. The first surface dry saturated aggregate tumbles inside the composite modified slurry with the stirring device. The composite modified slurry covers the outer surface of the first surface dry saturated aggregate, forming a liquid coating layer on the surface of the first surface dry saturated aggregate. The solid-liquid two-phase synergistic reshaping module outputs the first surface dry saturated aggregate with the liquid coating layer on its surface as wet initial coated aggregate.
[0049] In the solid-liquid two-phase co-remodeling module, the wet pre-coated aggregate is allowed to stand to leach out excess slurry. During the initial standing process, homologous active dry powder is sprinkled on the surface of the wet pre-coated aggregate. Then, mechanical rolling action is applied to produce powder embedded solid aggregate. During this process, the solid-liquid two-phase co-remodeling module transports the wet pre-coated aggregate to the screen component inside the solid-liquid two-phase co-remodeling module.
[0050] The wet initial coated aggregate is laid in a single layer on the surface of the screen component. The screen component has a physical mesh structure that allows fluid and excess slurry to pass through. The liquid coating layer on the surface of the wet initial coated aggregate in the initial static stage maintains an unsolidified fluid physical state. The free slurry on the surface of the wet initial coated aggregate that has not been combined with the first surface dry saturated aggregate passes through the mesh structure of the screen component under the action of gravity and detaches from the wet initial coated aggregate.
[0051] The powder spreading device inside the solid-liquid dual-phase synergistic reshaping module obtains homologous active dry powder. The powder spreading device is located above the screen component and contains an atomizing sieving structure. The powder spreading device sprays the homologous active dry powder in a dispersed powder flow state onto the wet initial coating aggregate on the surface of the screen component through the atomizing sieving structure. The particles of homologous active dry powder fall and adhere to the outside of the liquid coating layer on the surface of the wet initial coating aggregate.
[0052] The screen component is connected to a mechanical drive assembly. The solid-liquid dual-phase synergistic reshaping module controls the screen component to perform physical tumbling operations based on the mechanical drive assembly. The wet initial-coated aggregate in a single-layer flat state undergoes mechanical rolling with the screen component. The homologous active dry powder particles attached to the outside of the liquid coating layer are embedded into the surface structure of the liquid coating layer under the action of mechanical rolling. The homologous active dry powder particles combine with the liquid coating layer, and the solid-liquid dual-phase synergistic reshaping module produces powder embedded solid aggregate.
[0053] During the densification process of the composite modified slurry, the free fluid contained in the intermediate layer migrates towards the core layer and the outer isolation layer. The solid-liquid two-phase synergistic reshaping module controls the powder embedded solid aggregate to maintain a static state and establishes the driving force for fluid migration based on the difference in water potential state of each structural layer inside the powder embedded solid aggregate.
[0054] The structure system of powder embedded solid aggregate includes the first dry saturated aggregate forming the core layer, the composite modified slurry forming the intermediate layer, and the homologous active dry powder forming the outer isolation layer. The capillary channels inside the core layer contain liquid water and are in a fluid saturated state, while the outer isolation layer is in a dry state without liquid water.
[0055] The intermediate layer is located between the core layer and the outer isolation layer. The intermediate layer contains a free fluid with flow characteristics. Homologous active dry powder particles in the outer isolation layer come into contact with each other to form a stacked structure. The gaps between the particles in the stacked structure form capillary channels. The outer isolation layer in a dry state generates capillary water absorption potential energy in the capillary channel region.
[0056] The capillary channels inside the core layer generate water absorption potential energy for the free fluid inside the intermediate layer. A water potential gradient distribution is formed between the free fluid inside the intermediate layer and the core layer and the outer isolation layer. The free fluid inside the intermediate layer is pulled by the bidirectional capillary water absorption potential energy and migrates towards the core layer and the outer isolation layer.
[0057] The free fluid inside the intermediate layer migrates synchronously towards the core layer and the outer isolation layer, resulting in a decrease in the total volume of the free fluid inside the intermediate layer. The ordinary silicate cement particles, slag powder particles and silica fume particles contained in the intermediate layer undergo relative displacement under the boundary contraction caused by the reduction in fluid volume.
[0058] The aforementioned micro-particles move closer together, reducing the spacing between solid particles. Under conditions without external mechanical compaction, the solid-liquid dual-phase synergistic reshaping module reduces the pore volume inside the intermediate layer, completing the structural densification process of the composite modified slurry.
[0059] In the hydration curing and sealing module, the powder embedded solid aggregate is subjected to constant temperature and humidity conditions for curing reaction treatment. The homologous active dry powder on the surface of the powder embedded solid aggregate absorbs moisture to form an isolation structure without bonding strength, blocking the direct contact between particles. During this process, the hydration curing and sealing module relies on its internal hardware components to perform multi-stage curing operations.
[0060] The ventilation and drying component inside the hydration curing and sealing module receives the powder-embedded solid aggregate in a single-layer flat state. The ventilation and drying component is equipped with a ventilator, which provides airflow and maintains the ambient temperature at room temperature. The powder-embedded solid aggregate is kept in a static state inside the ventilation and drying component for 2 hours. The homologous active dry powder particles on the outermost side of the powder-embedded solid aggregate absorb some of the moisture seeping out of the composite modified slurry.
[0061] The homologous active dry powder contains S95 grade slag powder and 92 grade silica fume, which do not contain cement components. In a chemical environment lacking the strong alkaline activation conditions of ordinary silicate cement, the dry powder phase cannot undergo early hydration and cementation reaction. After absorbing water, the homologous active dry powder particles form a microparticle isolation shell on the outermost part of the solid aggregate embedded in the powder. The microparticle isolation shell covers the surface of the composite modified slurry. The microparticle isolation shell itself does not have structural bonding strength.
[0062] The ventilation and drying component transports the powder-embedded solid aggregate with a microparticle isolation shell on its surface to the standard curing box inside the hydration, curing and sealing module. The standard curing box is equipped with temperature and humidity control equipment, which provides a constant temperature of 20 degrees Celsius and a relative humidity of over 95%. Multiple powder-embedded solid aggregates come into contact in the accumulation area inside the standard curing box.
[0063] In the high-humidity environment of the standard curing chamber, the contact area between adjacent powder-embedded solid aggregates is the microparticle isolation shell around each of them. The microparticle isolation shell prevents the composite modified slurry inside the adjacent powder-embedded solid aggregates from having spatial contact. The microparticle isolation shell avoids the cross-particle matrix cross-linking phenomenon of the composite modified slurry during the hydration and hardening process.
[0064] The hydration-curing and sealing module sets the curing time parameter of the standard curing box to 28 days. After the set curing time, the composite modified slurry inside the powder-embedded solid aggregate reaches the hydration-hardened state. Due to the blocking effect of the microparticle isolation shell, the powder-embedded solid aggregate maintains the independent state of individual particles when it leaves the standard curing box, and no particle agglomeration occurs. The hydration-curing and sealing module produces cured modified aggregate with a complete external structure.
[0065] During the process of the hydration curing and sealing module performing secondary soaking and surface dehydration on the cured modified aggregate to transform it into a second surface-dry saturated modified aggregate and sealing the fluid absorption path on the surface of the cured modified aggregate, the hydration curing and sealing module moves the cured modified aggregate that has been cured into the secondary soaking tank inside the hydration curing and sealing module.
[0066] The secondary soaking tank is pre-filled with clean water. The hydration, solidification and sealing module controls the clean water inside the secondary soaking tank to completely submerge the solidified modified aggregate. The hydration, solidification and sealing module sets the soaking time of the solidified modified aggregate in the secondary soaking tank to 24 hours.
[0067] After the external hardening of the solidified modified aggregate, the surface of the composite modified slurry has partially closed capillary pores. During the set soaking time period, the clean water inside the secondary soaking tank seeps into the capillary pores on the surface of the composite modified slurry through capillary action, and the capillary pores on the surface of the composite modified slurry contain the clean water and reach a saturated state.
[0068] At the end of the soaking operation, the hydration, curing and sealing module controls the internally configured material transfer mechanism to remove the cured modified aggregate from the secondary soaking tank and place the cured modified aggregate on the permeable net inside the hydration, curing and sealing module to perform a static drainage operation. The hydration, curing and sealing module uses the internally configured second flexible water-absorbing wiping component to physically wipe the outer surface of the cured modified aggregate to remove the free water layer attached to the outer surface of the cured modified aggregate.
[0069] After the surface physical wiping action, the hydration curing and sealing module produces a second surface dry saturated modified aggregate. The outer surface of the second surface dry saturated modified aggregate is in a state without moisture adhesion, and the capillaries of the modified layer on the surface of the second surface dry saturated modified aggregate remain saturated. The second surface dry saturated modified aggregate blocks the transmission path of absorbing external mixing fluid in the subsequent concrete preparation process.
[0070] During the process of the multiphase matrix forming module controlling the mixing amount of the second surface dry saturated modified aggregate and natural crushed stone coarse aggregate according to the preset volume ratio parameters, the multiphase matrix forming module uses the internally configured data processing unit to obtain the total volume data of coarse aggregate per cubic meter. The data processing unit sets the total volume data of coarse aggregate per cubic meter to a fixed value of the total volume of coarse aggregate solids contained in each cubic meter of concrete system.
[0071] The data processing unit acquires the volume replacement rate parameter, controls the value range of the volume replacement rate parameter to be within the range of 20% to 60%, and sets the volume replacement rate parameter to the percentage of the volume of the modified aggregate in the second surface dry saturated state to the total volume of the coarse aggregate per cubic meter.
[0072] Set the volume substitution rate parameter as follows Set the total volume data of coarse aggregate per cubic meter as follows: Set the volume data of modified aggregate as follows: Set the volume data of natural crushed stone as The data processing unit processes the total volume data of coarse aggregate per cubic meter and the volume replacement rate parameter according to the equal volume substitution calculation rules, and calculates the volume data of modified aggregate and natural crushed stone. The calculation formula used is:
[0073]
[0074] The data processing unit extracts the apparent density parameters of the modified aggregate and the apparent density parameters of the natural crushed stone. The data processing unit multiplies the volume data of the modified aggregate with the apparent density parameters of the modified aggregate to calculate and output the mass feeding parameters of the modified aggregate. The data processing unit multiplies the volume data of the natural crushed stone with the apparent density parameters of the natural crushed stone to calculate and output the mass feeding parameters of the natural crushed stone.
[0075] The apparent density parameter of the modified aggregate is set as follows: The apparent density parameter of natural crushed stone is set as follows: Set the modified aggregate quality feeding parameters as follows: The parameters for feeding natural crushed stone were set as follows: The calculation formula for quality conversion performed by the data processing unit is as follows:
[0076]
[0077] The data processing unit sets the quality parameters of the non-coarse aggregate matrix material and the matrix water-cement ratio parameter to 0.5. To strictly match the mix design of the high-strength concrete foundation, the matrix cementitious material of the multiphase matrix forming module uses only ordinary Portland cement, without adding any other cementitious materials such as silica fume. The multiphase matrix forming module obtains ordinary Portland cement, mixing water, river sand, and water-reducing agent. The data processing unit sets the feed mass parameter of ordinary Portland cement to 380 kg / m³. 3 The data processing unit sets the mass parameter for the mixing water to be 190 kg / m³. 3 The data processing unit sets the feed mass parameter for river sand to 750 kg / m³. 3 The data processing unit sets the water-reducing agent dosage parameter to 7.6 kg / m³. 3 .
[0078] The multiphase matrix forming module uses its internal metering equipment to control and extract modified aggregates of the second surface dry saturated state according to the modified aggregate mass feeding parameters. The multiphase matrix forming module also uses its metering equipment to control and extract natural crushed stone coarse aggregates of the corresponding mass according to the natural crushed stone mass feeding parameters. The multiphase matrix forming module then transports the extracted modified aggregates of the second surface dry saturated state and the natural crushed stone coarse aggregates to the internal mixing equipment to perform multiphase mixing operations.
[0079] During the process of the multiphase matrix forming module transporting the extracted second-side dry saturated modified aggregate and natural crushed stone coarse aggregate to the internal mixing equipment to perform multiphase mixing, the multiphase matrix forming module uses the internally configured metering equipment to extract river sand with the corresponding feed mass parameters.
[0080] The multiphase matrix forming module transports river sand into the mixing equipment. The mixing equipment starts to rotate and performs dry mixing of the second-side dry saturated modified aggregate, natural crushed stone coarse aggregate and river sand, so that the multiphase aggregate particles achieve a uniform spatial distribution.
[0081] After the above dry mixing action is completed, the multiphase matrix forming module uses metering equipment to extract ordinary Portland cement with the corresponding feeding mass parameters. The multiphase matrix forming module then feeds the ordinary Portland cement into the mixing equipment. The mixing equipment then performs a second dry mixing of the ordinary Portland cement with the second surface dry saturated modified aggregate, natural crushed stone coarse aggregate, and river sand to produce a dry mixture.
[0082] The multiphase matrix forming module uses metering equipment to extract mixing water and water-reducing agent with corresponding feeding mass parameters. The multiphase matrix forming module simultaneously injects the mixing water and water-reducing agent into the mixing equipment containing the dry mixture.
[0083] The mixing equipment performs wet mixing operation. The multiphase matrix forming module sets the duration parameter of the wet mixing operation to be greater than or equal to 2 minutes. The dry mixture forms a fluid concrete mixture under the wet mixing operation.
[0084] The multiphase matrix molding module is equipped with a molding die and a mechanical vibration table. The multiphase matrix molding module pours the fluid concrete mixture into the molding die. The multiphase matrix molding module controls the mechanical vibration table to apply high-frequency mechanical vibration to the molding die containing the fluid concrete mixture, thereby expelling the gas contained in the fluid concrete mixture and producing a dense molded specimen.
[0085] The multiphase matrix molding module is equipped with a coating mechanism. The multiphase matrix molding module uses the coating mechanism to cover the surface of the compacted specimen with a moisturizing film at room temperature. The multiphase matrix molding module controls the compacted specimen to remain in a static state for 24 hours. After the static time ends, the multiphase matrix molding module uses the demolding mechanism configured inside to remove the molding mold and obtain the demolded concrete matrix.
[0086] The multiphase matrix forming module transports the demolded concrete matrix to the internally configured constant temperature standard curing chamber. The constant temperature standard curing chamber is equipped with a temperature and humidity control unit. The multiphase matrix forming module controls the ambient temperature of the constant temperature standard curing chamber to be 20±2 degrees Celsius and the relative humidity parameter to be greater than or equal to 95% through the temperature and humidity control unit. The demolded concrete matrix contains a mortar matrix in the process of hydration. The mortar matrix is formed by mixing and hydrating ordinary silicate cement, mixing water and river sand.
[0087] In the constant temperature standard curing room, the 92 grade silica fume particles remaining on the surface of the second dry saturated modified aggregate come into contact with the mortar matrix. The 92 grade silica fume particles in the incompletely hydrated state form nucleation nodes for crystal growth inside the demolded concrete matrix. The hydration products generated by ordinary silicate cement extend to the surface of the second dry saturated modified aggregate through the nucleation nodes.
[0088] The hydration products form a crystalline interwoven structure at the interface between the modified aggregate in the second dry saturated state and the mortar matrix. The crystalline interwoven structure establishes a continuous chemically bonded transition layer around the modified aggregate in the second dry saturated state. After a 28-day curing period, the multiphase matrix molding module produces a high-strength modified concrete product containing an internal aggregate support layer, a middle chemically bonded transition layer, and an external high-strength mortar matrix.
[0089] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing high-strength concrete using pre-coated modified coal gangue aggregate, characterized in that, Includes the following steps: Step 1: Obtain raw coal gangue aggregate, and perform fluid soaking and surface physical dehydration treatment on the raw coal gangue aggregate to produce first surface-dry saturated aggregate; the first surface-dry saturated aggregate is in a physical state in which there is no free water on the surface and the internal pores are saturated with fluid. Step 2: Obtain the first part of cement, slag powder, silica fume and the first part of mixing water, mix the first part of cement, part of the slag powder, part of the silica fume and the first part of mixing water to produce a composite modified slurry in a fluid suspension state; The remaining slag powder is extracted and mixed with the remaining silica fume to produce homologous active dry powder in a solid dry powder state. Step 3: Place the first surface-dry saturated aggregate into the composite modified slurry and perform physical stirring to produce wet initial-coated aggregate; allow the wet initial-coated aggregate to stand to drain excess slurry, and during the initial standing process, sprinkle the homologous active dry powder onto the surface of the wet initial-coated aggregate, and then apply mechanical rolling action to produce powder-embedded solid aggregate; so that within the structure system of powder-embedded solid aggregate, the free fluid contained in the composite modified slurry migrates to the outside and inside to achieve densification; Step 4: Apply constant temperature and humidity conditions to the powder-embedded solid aggregate for curing reaction treatment. After the curing reaction is completed, cured modified aggregate is produced. Then, the cured modified aggregate is subjected to secondary soaking and surface dehydration to block the fluid absorption path on the surface of the cured modified aggregate and transform the cured modified aggregate into a second surface-dry saturated modified aggregate. Step 5: Control the mixing amount of the second surface-dry saturated modified aggregate and the natural crushed stone coarse aggregate according to the preset volume ratio, and mix the second surface-dry saturated modified aggregate and the natural crushed stone coarse aggregate. Add river sand, the second part of cement, water-reducing agent and the second part of mixing water for segmented dry and wet mixing. After the mixing mixture is filled and shaped, physically vibrated and cured at constant temperature, the high-strength modified concrete product is output.
2. The method for preparing high-strength concrete by pre-coating and modifying coal gangue aggregate according to claim 1, characterized in that, Step one, the process of performing fluid soaking and surface physical dehydration treatment on the raw coal gangue aggregate, includes: Untreated block coal gangue is mechanically crushed and screened in multiple stages to retain continuously graded particles with a particle size range of 5 mm to 20 mm as the original coal gangue aggregate. The raw coal gangue aggregate is placed into a soaking tank pre-filled with clean water, and the height of the clean water is controlled to exceed the top layer of the raw coal gangue aggregate. The raw coal gangue aggregate is kept submerged in the clean water for 48 hours, forming a fluid saturation zone in the internal structure of the raw coal gangue aggregate. At the end of the soaking operation, the raw coal gangue aggregate is removed from the soaking tank and placed on a permeable net to perform a static water removal operation. The outer surface of the raw coal gangue aggregate is physically wiped using a flexible water-absorbing wiping component to remove the free water layer and produce the first surface-dry saturated aggregate.
3. The method for preparing high-strength concrete using pre-coated modified coal gangue aggregate according to claim 1, characterized in that, In step two, the first portion of cement is ordinary Portland cement, the slag powder is S95 grade slag powder, and the silica fume is 92 grade silica fume. The material metering operation follows the following proportioning principle: The ratio of the total mass of the ordinary silicate cement to the total mass of the S95 grade slag powder is set to 9:1, and the ordinary silicate cement and the S95 grade slag powder are combined to form a composite cementitious material base. The total mass of the added Grade 92 silica fume is controlled to be 5% of the total mass of the composite cementitious material substrate; The water-cement ratio is set to 0.5, which means that the ratio of the mass of the first batch of mixing water to the total mass of the composite cementitious material substrate and the grade 92 silica fume is 0.
5. The internal material mass ratio of the homologous active dry powder is controlled such that the mass of the remaining 92-grade silica fume extracted is 5% of the mass of the remaining S95-grade slag powder extracted.
4. The method for preparing high-strength concrete by pre-coating and modifying coal gangue aggregate according to claim 3, characterized in that, The specific process of step two includes: The S95 grade slag powder is divided into a first slag powder portion as part of the slag powder and a second slag powder portion as the remaining slag powder, and the 92 grade silica fume is divided into a first silica fume portion as part of the silica fume and a second silica fume portion as the remaining silica fume. All of the ordinary silicate cement, the first slag powder portion, the first silica fume portion, and all of the first portion of mixing water are fed into a mixing device for mixing, so that the solid particles are mixed in the first portion of mixing water to form a suspended liquid phase, and the suspended liquid phase is output as the composite modified slurry. The second slag powder portion and the second silica fume portion are fed into a dry powder mixing device to perform physical grinding and stirring operations, and are uniformly mixed to produce the homologous active dry powder.
5. The method for preparing high-strength concrete by pre-coating and modifying coal gangue aggregate according to claim 1, characterized in that, The specific preparation process in step three includes: The first surface-dry saturated aggregate is put into the mixing device in operation, so that the composite modified slurry covers the outer surface of the first surface-dry saturated aggregate to form a liquid coating layer, and the wet initial coated aggregate is produced. The wet initial coated aggregate is conveyed to a screen component with a physical mesh structure and laid in a single layer, so that the surface free slurry is separated through the mesh structure by gravity. The homologous active dry powder is sprayed onto the wet initial coating aggregate in a dispersed powder flow state through the atomizing sieving structure of the powder spreading device, so that the particles of the homologous active dry powder adhere to the outside of the liquid coating layer. The screen component is controlled to perform physical tumbling action by means of a mechanical drive assembly, so that the homologous active dry powder particles attached to the outside of the liquid coating layer are embedded into the surface structure of the liquid coating layer under the action of mechanical rolling force, producing the powder embedded solid aggregate.
6. The method for preparing high-strength concrete by pre-coating and modifying coal gangue aggregate according to claim 5, characterized in that, Within the powder-embedded solid aggregate structure system, the first surface-dry saturated aggregate constitutes the core layer, the composite modified slurry constitutes the intermediate layer, and the homologous active dry powder particles constitute the outer isolation layer. The densification mechanism in step three includes: The powder-embedded solid aggregate is kept in a static state so that the core layer, which is in a fluid saturation state, can generate water absorption potential energy for the free fluid inside the intermediate layer. In the dry state, the homologous active dry powder particles in the outer isolation layer come into contact with each other to form a stacked structure, so that the gaps between the particles inside the stacked structure form capillary channels and generate capillary water absorption potential energy. The free fluid inside the intermediate layer is pulled towards the core layer and the outer isolation layer by the bidirectional capillary water absorption potential energy, resulting in the reduction of fluid volume and the boundary contraction effect. This causes the solid particles contained in the intermediate layer to undergo relative displacement and move closer to each other, thus completing the structural densification of the composite modified slurry.
7. The method for preparing high-strength concrete by pre-coating and modifying coal gangue aggregate according to claim 1, characterized in that, The specific process of step four includes: A ventilator is used to provide airflow to the ventilation and drying components and maintain room temperature, so that the single-layer flat-laid powder embedded solid aggregate is kept in a static state for 2 hours. The outermost homologous active dry powder particles absorb moisture to form a microparticle isolation shell with no bonding strength. The powder-embedded solid aggregate is transported to a standard curing chamber, where a constant temperature of 20 degrees Celsius and a relative humidity of over 95% are provided by a temperature and humidity control device. The curing time is set to 28 days to produce the solidified modified aggregate. The cured modified aggregate is transferred into a secondary soaking tank filled with clean water, and the soaking time is controlled to be 24 hours to saturate the surface capillaries. Then it is removed and placed on a permeable net, and a flexible water-absorbing wiping component is used to physically wipe it to remove the free water layer attached to the outer surface, producing the second surface-dry saturated modified aggregate.
8. The method for preparing high-strength concrete by pre-coating and modifying coal gangue aggregate according to claim 1, characterized in that, In step five, the calculation process for controlling the mixing amount includes: Determine the total volume of coarse aggregate per cubic meter and control the volume replacement rate to be within the range of 20% to 60%. According to the equal volume substitution calculation rule, the volume of modified aggregate is calculated by multiplying the total volume of coarse aggregate per cubic meter by the volume substitution rate, and the volume of natural crushed stone is calculated by multiplying the total volume of coarse aggregate per cubic meter by the difference between 1 and the volume substitution rate. Obtain the apparent density of the modified aggregate and the apparent density of the natural crushed stone. Multiply the volume of the modified aggregate by the apparent density of the modified aggregate to obtain the feed mass of the modified aggregate. Multiply the volume of the natural crushed stone by the apparent density of the natural crushed stone to obtain the feed mass of the natural crushed stone.
9. The method for preparing high-strength concrete by pre-coating and modifying coal gangue aggregate according to claim 8, characterized in that, Step five, the process of segmented dry and wet mixing, includes: The modified aggregate and the natural crushed stone are extracted according to the mass of the modified aggregate and the mass of the natural crushed stone, respectively, and the river sand of the corresponding mass is extracted and transported into the mixing equipment to start the rotation and perform dry mixing. After the dry mixing action is completed, the second part of cement corresponding to the feed mass is extracted and fed into the mixing equipment for secondary dry mixing to produce a dry mixture. The second portion of mixing water and the water-reducing agent are extracted and simultaneously injected into the mixing equipment containing the dry mixture to perform a wet mixing operation. The duration of the wet mixing operation is greater than or equal to 2 minutes, producing a fluid concrete mixture with fluidity.
10. The method for preparing high-strength concrete by pre-coating and modifying coal gangue aggregate according to claim 9, characterized in that, Step five, the process of filling and molding, physical vibration and constant temperature curing includes: The fluid concrete mixture is poured into the mold, and a high-frequency mechanical vibration is applied by a mechanical vibration table to expel gas and produce a dense molded specimen. After covering the surface with a moisturizing film at room temperature and maintaining a static state for 24 hours, the molding mold is removed to obtain the demolded concrete substrate. The demolded concrete substrate is then transported to a constant temperature standard curing room, where the ambient temperature is controlled at 20±2 degrees Celsius and the relative humidity is greater than or equal to 95%. The goal is to enable silica fume particles in an incompletely hydrated state to form nucleation nodes for crystal growth within the demolded concrete matrix, allowing hydration products to form an interwoven crystal structure at the interface, establishing a continuous chemically bonded transition layer, and producing the high-strength modified concrete product after a 28-day curing period.